2005
DOI: 10.1002/macp.200500008
|View full text |Cite
|
Sign up to set email alerts
|

On the Interpretation of X‐Ray Diffraction Powder Patterns in Terms of the Nanostructure of Cellulose I Fibres

Abstract: Summary: The average lateral dimensions of cellulose microfibrils in paper sheets can be determined from the width of X‐ray Bragg peaks at half the maximum height. The method assumes it is the finite size of the crystallite which is the main contributor to peak broadening in the directions orthogonal to the long axis of the crystallite. This assumption is examined in the context of samples from different botanical sources, of varying crystallinity and cellulose content and the various instrumental sources of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
163
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(186 citation statements)
references
References 42 publications
17
163
0
6
Order By: Relevance
“…This will result in lower crystallinity values because a higher contribution of the amorphous component would be subtracted. The suggestion is supported by both the diffractrogram deconvolution method which suggests a value of 21.5° (Garvey et al 2005) and the authors' current WAXS data where for amorphous Whatman CC31 sample a value of 21°was observed (Fig. 3j).…”
Section: Ball Milled Samplessupporting
confidence: 57%
“…This will result in lower crystallinity values because a higher contribution of the amorphous component would be subtracted. The suggestion is supported by both the diffractrogram deconvolution method which suggests a value of 21.5° (Garvey et al 2005) and the authors' current WAXS data where for amorphous Whatman CC31 sample a value of 21°was observed (Fig. 3j).…”
Section: Ball Milled Samplessupporting
confidence: 57%
“…Individual crystalline peaks were first extracted by a curve-fitting process from the diffraction intensity profiles [20,21,22]. The CI was calculated by dividing the diffractogram area of crystalline cellulose by the total area of the original diffractogram.…”
Section: The Crystallinity Indexmentioning
confidence: 99%
“…The crystalline domain size of the Iβ cellulose was calculated via the Scherrer (1918) equation from the (002) reflection, to provide commonly quoted results (Garvey et al 2005). The alternative whole powder pattern modelling (WPPM) (Scardi and Leoni 2002), which gives a more physical quantitative result, was also tentatively employed.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%